Periventricular white matter hyperintensities are associated with gait and balance in patients with minor stroke - Su, Chen; Yang, Xiaoyu; Wei, Shuqi; Zhao, Renliang (Frontiers in Neurology, 2022)
Objective Cerebral small vessel disease (CSVD) is associated with gait and balance deficits in older adults. However, the effect of CSVD-related brain injury on post-stroke mobility is unknown. This study aimed to investigate the association of CSVD with gait and balance impairment after a minor stroke. Methods A total of 273 patients with a minor stroke (NIHSS ≤ 5 points) who were hospitalized at the Affiliated Hospital of Qingdao University were enrolled. The manifestations of white matter hyperintensities (WMH), lacunes, enlarged perivascular spaces (EPVS), and cerebral microbleeds (CMB) were statistically analyzed according to magnetic resonance imaging results, and the total burden score of CSVD was calculated. Gait function was assessed by a 6-m walking speed test, and balance function was assessed by the timed-up-and-go (TUG) test. Linear regression analysis was applied to determine the association after adjusting for key variables. Results The correlation results showed that in patients with minor stroke, age, sex, smoking history, and the infarct site were associated with gait speed, and age and the infarct site were associated with the TUG test. In the univariate linear regression model, periventricular white matter hyperintensities (PVWMH), deep white matter hyperintensities (DWMH), and the total burden of CSVD were correlated with gait speed, while only PVWMH correlated with the TUG test. After adjusting for confounders, only PVWMH were independent predictors of gait speed (β = −0.089, p < 0.05) and the TUG test (β = 0.517, p < 0.05). Conclusions Our study confirmed that CSVD is associated with gait and balance disorders after a minor stroke. PVWMH are independent predictors of gait and balance disorders in patients with minor stroke. These findings should be confirmed in larger prospective studies.